Enthalpy analysis of Ce–Mg–Ni–H formation based on extended miedema theory: Investigation of selected Ce2MgNi2–H2. (19th January 2021) - Liu, Zhuocheng; Li, Yiming; Ruan, Fei; Zhang, Guofang; Zhao, Ming; Liu, Zhongxin; Zhang, Jieyu
Abstract: In this paper, an extended Miedema's model is constructed to illustrate its applicability to estimating the solid-solution enthalpies of Ce–Mg–Ni–H hydrides, adopting the range of an optimized stoichiometry alloy in the contour map of solid-solution state enthalpy. Ce2 MgNi2 alloy is designed to investigate its hydrogen storage properties, and its main phase is confirmed with X-ray diffraction characterizations. The alloy shows a good activation ability and the pressure component temperature plateau is extremely flat. The formation enthalpy of Ce2 MgNi2 –H2 is calculated with the extended Miedema theory, with the least enthalpy value of −59.1 kJ/mol for the corresponding hydrogen content of 1.64 wt %. Both experimental and theoretical data of the hydrogen-containing alloy confirm that the thermodynamic enthalpy of the quaternary Ce2 MgNi2 –H2 is consistent with that of the experimental results. When calculating the formation enthalpy of hydrogen and metal, the enthalpy of the elastic contribution between metal and hydrogen was considered, generally improving the versatility and accuracy of the calculation. Moreover, the extended Miedema's model is used to predict the hydrogen storage performance. Highlights: Formation enthalpies of hydrogen-containing quaternary are calculated by extended Miedema's model. Estimated maximum hydrogen content is found to corresponding to the most negative enthalpy. Maximum hydrogen capacity of Ce2 MgNi2 alloy reaches 1.57 wt. % H2, this is consistent with theoretical H-storage 1.64 wt. % H2 . Hydride formation enthalpy of Ce2 MgNi2 alloy is −63.7 KJ/mol. It keeps with −59.1 KJ/mol H2 obtained by Van't Hoff equation.